PERFORMANCE ANALYSIS OF UNSIGNALIZED INTERSECTIONS AND ROAD SECTIONS USING VISSIM SOFTWARE - Amar Mufhidin; Nur Aflah Dzakwaniah Chaniago (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
The Kodim intersection is one of the intersections at Jalan Raya Sawangan. Identifying vehicle traffic, performance, and potential remedies at the Kodim intersection and Jalan Raya Sawangan was the goal of this study. The information gathered from the survey results, the research technique employs a strategy from the PKJI (Pedoman Kapasitas Jalan Indonesia) and a simulation utilizing the PTV Vissim program. Based on the results of data analysis and processing, the busiest traffic flow at the Kodim intersection occurred on Weekday at 17.30–18.30 WIB with a degree of saturation value of 1,391 and the LoS value is F. Analysis of the road section also obtained the largest volume of vehicles on Weekday at 17.15–18.15 WIB, the degree of saturation value is 1.49, so the Los value is F. By carrying out several repair solutions, the best service level value is obtained for the repair solution by making a flyover. The solution of making a flyover produces a degree of saturation value of 0.382, so that the Level of Service (Los) value of the intersection is obtained at level B. The resulting degree of saturation value is below 0.85, as required in the PKJI 2014.